Cable Tilt Actuator for an Aircraft - Waide, William Martin (2025)
In one aspect the subject matter herein describes a cable tilt actuator for an aircraft propulsion unit. One embodiment comprises: a cable spool, fore and aft cable sections, a compression beam, a compression beam guide, and a linear actuator. As the linear actuator drives the compression beam, relative rotation is imposed between the compression beam and the spool. Described, in one aspect, is an embodiment configured to tilt an aircraft propulsion unit.